Seroprevalencia de Brucella canis en la población canina del centro de zoonosis de la ciudad de Villavicencio (2023)
Background: The Brucella canis has become a problem, such as zoonotic disease, which causes abortions usually 6-8 weeks of gestation, in the postconception of females, and in males causes inflammation of the scrotal sacs and infection in the testicles. Objective: To determine the prevalence of Brucella canis from the canine population that enters the center of zoonoses of the city of Villavicencio, META-Colombia. Materials and Methods: Male and female canines were used in reproductive age of the animals entering the center of the city of zoonoses of Villavicencio-Meta Colombia. Under simple random sampling completely random, studied 150 canines during 5 months divided into groups of 30 animals, which underwent a full diagnostic examination and blood sample and laboratory diagnostic AIDS for the technique of agglutination for Brucella canis. Results: We found a seroprevalence of 9.3% (14 dogs), 7 males and 7 females. Conclusions: With the seropositivity found by Brucella canis in dogs from the center of zoonoses, means a risk to public health of the institution and of the city of Villavicencio, by the great significance of stray dogs, which involves making a greater epidemiological research.